Managing innovation and standards : a case in the european heating industry (2019)
How can innovators manage the seemingly paradoxical relationship between creating radical innovations and complying with external requirements that aim to fx solutions in place? Although businesses face this question whenever they want to bring a new product to market, there is surprisingly little research on the topic. This observation motivated me to investigate how innovative companies deal with standards, as a key example of the external requirements that businesses face. A review of the literature in Chapter 1 shows that standards indeed have a substantial impact on innovation. Depending on the specifc standards, these effects can be positive (e.g. facilitating market access, defning interfaces to supporting infrastructures), but also hinder innovation (e.g. through lock-in). Although the relationship between innovation and standards is not as paradoxical as it frst seems, literature confrms its importance for innovators. To understand how they address this topic, I conducted an in-depth grounded theory case study of the micro Combined Heat and Power (mCHP) technology’s development in Europe. As Chapter 2’s introduction to the case shows, this radical sustainable innovation is ideal for understanding standards in the context of innovation. Based on in-depth interviews with the key involved actors, I was able to trace in much detail how the technology, standards, and regulation co-evolved.